Training Personnel for the “Green” Economy: The Role of Education, Professional Retraining, and New Competencies in Uzbekistan (KIUT Publication, 2025)
The “green” economy is understood as an economic system that improves people’s well-being and social justice while simultaneously reducing environmental risks and resource scarcity. Achieving this model requires a transition from traditional industries to environmentally sustainable ones, which inevitably leads to a transformation of the labor market. International studies emphasize that the development of human capital is a key condition for the “greening” of the economy.